Prevalência de aconselhamento para atividade física na Atenção Básica à Saúde: uma revisão sistemática - Moraes, Sheylane de Queiroz (2019)
Counseling has shown promise for behavior change. This study aims to carry out a systematic review on the prevalence of counseling for the practice of physical activity offered by health professionals and received by users in the context of Primary Health Care. We reviewed the journal bases PsycINFO, EBSCOhost, PubMed, ScienceDirect, Web of Science, LILACS and SciELO. The risk of bias was evaluated in all articles. In total, 44 articles were included, of which 21 investigated advice provided by health professionals and 23 analyzed advice received by users. The prevalence of counseling ranged from 11.8% to 95.0% among professionals (60.2 ± 22.7%) and 4.5% to 61.6% among users (36.6 ± 14.2%). Doctors are the most researched professionals. Users with risk factors for chronic diseases are the most reported to receive counseling. Counseling is still incipient in Primary Health Care, especially because of the low perception of counseling received by users. There is a need to standardize methods to evaluate physical activity counseling, especially in the kind and in the form of advice.